PENGARUH OPTIMUM STIMULATION LEVEL TERHADAP VARIETY-SEEKING PADA BISNIS RITEL - SALIM, IVANDER WIRYA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Research themed Variety-Seeking behavior concept has been long developed. In 1982, McAlister conducted empirical research on variety-seeking behavior. However, The studies about Variety-Seeking behavior in general are more focused on the external factors. While internal factors also have an equal important role in the process of Variety-Seeking. Therefore, in this paper will be described on the effect of optimum stimulation level, which is one of the internal customer psychologically aspects. The results of article indicate that the optimum stimulation level has an influence on variety seeking; it is consistent with Steenkamp and Baumgartner on Mayasari (2008) study, which states that the Variety-Seeking considered as a tool or a way to procure stimulation in purchase behavior by selecting the known object choice. Based on the literature search, Raju on Mayasari (2008), Wikie on Mayasari (2008), Bawa on Mayasari (2008), supported by research conducted by Steenkamp and Baumgartner on Mayasari (2008), it can be concluded that, individuals who are in optimum stimulation level cause individuals to do Variety-Seeking, if consumers are in a bored condition caused by the presence of a monotonous stimuly stores, so consumers will be doing on Variety-Seeking of the other stores to get something new and different.